2017
DOI: 10.1002/jcc.24877
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigation inspired “on water” reaction for hydrobromic acid‐catalyzed Friedel–Crafts–type reaction of β‐naphthol and formaldehyde

Abstract: The mechanism of the HBr-catalyzed Friedel-Crafts-type reaction between β-naphthol and HCHO was investigated by DFT to improve this reaction. The HBr-H O co-catalyzed the preferential pathway undergoes the concerted nucleophilic addition and hydrogen shift, stepwise followed by H O elimination and the CC bond formation. The origin of the high catalytic activity of HBr is ascribed to CH···Br and OH···Br interactions, which suggest that the active species is Br . Moreover, water molecules efficiently assist i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…They concluded that while the implicit solvent effects of polar solvents do not substantially modify the gas-phase energies found along a pathway, the explicit inclusion of one solvent molecule favors the reaction to take place via a less-strained transition state. In light of the research work studied by Zheng and Zhang, we find that the interaction between the water molecule cluster and reactants is very beneficial to the “on water” reaction; especially, it is the most favorable that the cluster models with two water molecules (called the two-water cluster) and the three water molecules (called the tri-water cluster) assist the intramolecular or intermolecular proton hydrogen transfer. Similarly, Jung and Marcus implemented the three-site water model to indicate that the hydrogen bond-mediated lowering of the energy barrier was the key origin for the enhanced acceleration of the cycloaddition reaction between quadricyclane and dimethyl azodicarboxylate .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that while the implicit solvent effects of polar solvents do not substantially modify the gas-phase energies found along a pathway, the explicit inclusion of one solvent molecule favors the reaction to take place via a less-strained transition state. In light of the research work studied by Zheng and Zhang, we find that the interaction between the water molecule cluster and reactants is very beneficial to the “on water” reaction; especially, it is the most favorable that the cluster models with two water molecules (called the two-water cluster) and the three water molecules (called the tri-water cluster) assist the intramolecular or intermolecular proton hydrogen transfer. Similarly, Jung and Marcus implemented the three-site water model to indicate that the hydrogen bond-mediated lowering of the energy barrier was the key origin for the enhanced acceleration of the cycloaddition reaction between quadricyclane and dimethyl azodicarboxylate .…”
Section: Introductionmentioning
confidence: 99%